Movement Education Programme in Elementary Schools in District Pulwama of UT Jammu and Kashmir (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The subjects for this study were 50 boys and girls were selected. These subjects between ages of 5 to 7 years were studying in primary school of district pulwama from the school. All subjects were randomly selected for the equal ratio of 5 to7 years of age group. From the attendance register of the students the age was calculated separately and Subjects were divided into two groups i.e. experimental (N1=25) and Control group (N2=25). In the present Study, following Physical Variables were selected: Shuttle run and Standing broad jump. Shuttle run measures ability and speed. Standing broad jump-it measures explosive leg strength. In this study paired t – test was employed to know the impact of movement education programme in elementary schools. In this study level of significance was set at 0.05. Results describes a significant difference in the experimental group and an insignificant difference in control groups in both variables at level of significance 0.05